Does Social Embedding Influence Banking Habits? A Case of India. (August 2016) - Roy, Pinaki; Sapre, Amey
This article attempts to empirically investigate the relationship of social embeddedness and banking behaviour in India. Social embeddedness is a construct that in general refers to non-market societies or activities, such as customs, traditions and reciprocity, that dominate the conduct of societies. Using the India Human Development Survey (IHDS) 2005 household survey data, we construct a weighted average score of social embedding as captured by memberships in societies and network groups to estimate their impact on the likelihood of a household's access to banking. Findings show that social embeddedness has a positive and substantial impact on improving a household's access to banking. We argue that social embedding can serve as an effective means to enhance the reach and access of financial services if conventional inclusion programmes were to utilize and exploit such social channels. JEL Classification: C23, D71, G20